ANALYSIS OF THE FACTORS AFFECTING ON THE INDUSTRY AND PRODUCTION OF ELECTRICAL ENERGY IN THE DOHUK GOVERNORATE - Hassam, Ibrahim Khishman; Ameen, Azad Muhammed (Journal of Duhok University, 2018)
This research aims at studying the most important factors influencing the endurance of the industry and production of Electrical Energy in Dohuk Governorate (fuel, energy, market, transport, water, labor, land availability, environmental protection from pollution) to show their availability in the study area and the impact of each of them separately To end this activity in the Governorate. At the end of the study we found a relationship between these factors and the end of the Electricity industry according to the available data on the four production stations (Mas Global (Quashy), Baadari, Dohuk station, Akri station). However, they were subject to planning and strategy factors adopted by local government policies And regional issues.